Pengaruh Nilai Tukar Mata Uang dan Inflasi terhadap Profitabilitas di Bank Syariah: Studi Analisis pada Bank Muamalat, Bank Mandiri Syariah dan Bank Mega Syariah Periode 2011-2015 - Rafika Rahmawati; Hilda Mailil Haque (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2018)
This study aims to analyze the influence of currency exchange rates and inflation on the profitability of sharia banks as measured by return on equity as dependent or dependent variable. This study used a sample of three Sharia Commercial Banks, the data obtained are secondary data based on financial statements within 5 years and taken for a month. Sampling method used is purposive sampling method and tested statistic used is multiple linear regression test. The empirical results of this study indicate that there are simultaneous effects on exchange rate variables and inflation on return on equity. The results of this study also shows that currency exchange rate variables partially affect the return on equity on each Sharia Commercial Bank, while inflation does not partially affect the return on equity in each of the Sharia Commercial Banks namely Muamalat Bank, Mandiri Shari’ah Bank, and Mega Shari’ah Bank.